2011
DOI: 10.1007/s10657-011-9232-0
|View full text |Cite
|
Sign up to set email alerts
|

The law and economics of international sex slavery: prostitution laws and trafficking for sexual exploitation

Abstract: International trafficking in humans for sexual exploitation is an economic activity driven by profit motives, and up to four million people are estimated to be exploited by human traffickers each year. Laws regarding commercial sex influence the profitability of trafficking and may thus affect the inflow of trafficking to a country. Using two recent sources of European cross country data we show that trafficking of persons for commercial sexual exploitation (as proxied by the data sets we are using) is least p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 28 publications
3
65
1
5
Order By: Relevance
“…Human trafficking researchers discuss law enforcement and the level of corruption as important factors, both in origin and destination countries (Akee et al 2010(Akee et al , 2014Cho, Dreher, & Neumayer, 2013;Jakobsson & Kotsadam, 2013). Besides the general rule of law, specific antitrafficking measures are also crucial to addressing the problem (Cho et al 2014;Cho & Vadlamannati, 2012;Potrafke, 2013).…”
Section: Policy and Institutional Effortsmentioning
confidence: 99%
“…Human trafficking researchers discuss law enforcement and the level of corruption as important factors, both in origin and destination countries (Akee et al 2010(Akee et al , 2014Cho, Dreher, & Neumayer, 2013;Jakobsson & Kotsadam, 2013). Besides the general rule of law, specific antitrafficking measures are also crucial to addressing the problem (Cho et al 2014;Cho & Vadlamannati, 2012;Potrafke, 2013).…”
Section: Policy and Institutional Effortsmentioning
confidence: 99%
“…From this perspective, supporting some form of criminalization has the potential to reduce harm to those who are financially induced or coerced. It also appears that criminalization discourages buyers [43,44], reducing the demand for sellers, which in turn worsens commerce for traffickers and reduces trafficking [45]. However, arrest can compound adversity for sellers, particularly those from marginalized populations [46], and enforcement can be selectively used against buyers and brokers [47] in a racist way.…”
Section: Policy Options For Addressing Commercial Sexmentioning
confidence: 99%
“…Although there is variation in how the Nordic model is implemented across countries [49], it is often promoted by those involved in anti-trafficking advocacy [50,51]. Four separate studies have found that sex trafficking is reduced under this model [40,41,45,52], and some analyses indicate that the Nordic model provides better support services to sellers than other systems [53,54], although the results have been called into question [42,48]. One criticism of the Nordic model is that any supposed benefit of legalizing selling is offset by the fact that buyers are still penalized, which means that sellers must continue to meet buyers under dangerous conditions [55].…”
Section: Policy Options For Addressing Commercial Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Slično ideji potpune zabrane prostitucije, u pitanju je američki izum koji se izvozi po svetu iako je u mestu porekla imao polovičan uspeh. Razlog za to je što stvara dodatne troškove 5 Stavovi radikalnih feminista podrobno su izloženi u: K. Miriam prostitutkama da bi se uspešno bavile svojim zanatom. Ono gde je ova kriminalna politika bila uspešna jeste skretanje pažnje javnosti na polno osnovano podvajanje u praktičnom sprovođenju normative koja se odnosi na prostituciju.…”
Section: Vrednosni Stavovi Radikalnih Feministaunclassified